2017
DOI: 10.1590/2359-3997000000307
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node characteristics as predictors of recurrence/persistence in the neck and distant metastases in differentiated thyroid cancer

Abstract: Objective: The aim of this study was to evaluate the association between this characteristic and outcomes in patients with lymph node metastasis in a Brazilian cohort. Subjects and methods: This study examined a retrospective cohort of adult patients diagnosed with differentiated thyroid cancer and lymph node metastases from 1998 to 2015 in two referral centers. Number, location, size and extranodal extension (ENE) of metastatic lymph nodes were assessed and correlated with response to initial therapy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…2 Papillary thyroid cancer and follicular thyroid cancer are the major subtype of thyroid cancer, and frequently have a favorable prognosis. 5 Thus, it is necessary to identify reliable biomarkers for predicting clinical progression and prognosis, which may be useful to improve the survival of thyroid cancer patients. 5 Thus, it is necessary to identify reliable biomarkers for predicting clinical progression and prognosis, which may be useful to improve the survival of thyroid cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Papillary thyroid cancer and follicular thyroid cancer are the major subtype of thyroid cancer, and frequently have a favorable prognosis. 5 Thus, it is necessary to identify reliable biomarkers for predicting clinical progression and prognosis, which may be useful to improve the survival of thyroid cancer patients. 5 Thus, it is necessary to identify reliable biomarkers for predicting clinical progression and prognosis, which may be useful to improve the survival of thyroid cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the survival rates of patients with PTC and FTC have been reported to be significantly associated with DM (14,15). Lymph node metastasis (LNM) status and tumor size are also associated with DM in patients with PTC (16,17). Previous studies have also identified ETE and LNM status as independent risk factors for DM in patients with DTC (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying patients at risk of DM is therefore a critical step in the management of DTC so that appropriate treatments can be initiated. A number of prognostic factors including age, gender, histology, tumour size, vascular invasion (VI), lymph node metastasis (LNM) and extra‐thyroidal extension (ETE) have been identified as predictors of DM in DTC 5–8,11–21 . However, there is ongoing debate as conflicting results have been illustrated by other investigators.…”
Section: Introductionmentioning
confidence: 99%